Perspectives on Secession
IX, 142 p. 18 illus., 11 illus. in color.
Keywords: This book explores the changing nature of secessionist attempts in connection with rapidly evolving geopolitical and technological landscapes. By presenting theoretical chapters as well as case studies on various secessionist movements around the globe, the contributing authors study a range of topics, including: the role of the media in secessionist conflicts; secessionist referenda and the viability of secessionist attempts in terms of their internal dimension; and external support and interference. The book will appeal to political scientists and international relations scholars who are interested in the processes, politics and geopolitical implications of secessionist movements.